Consistency of Sharia Asset Development with Gold Investment Financing at BMT: Case Study of Murabahah Contract Against Sharia Accounting - Putri, Tri Asti Sari; Setiawati, Erma; Trisnawati, Rina (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the consistency of sharia in the development of assets with gold investment financing at BMT with a case study on the Murabahah contract. The research method used is a qualitative approach with data collection techniques through interviews and observations. The study shows that the implementation of the principles of sharia contracts in the Murabahah contract at BMT is still not fully sharia after being integrated with the Maqashid Sharia Theory by Asy-syatibi which involves Maslow's Hierarchy of Needs Theory. This is caused by several factors such as a lack of understanding of the principles of sharia transaction contracts, weak supervision of the sharia board at the institution. To improve sharia consistency in the development of assets with gold investment financing at BMT through the Murabahah contract, it is recommended that BMT improve the understanding and competence of its workforce in the principles of sharia economics, strengthen the supervision system, and conduct dialogue and consultation with sharia law experts in order to obtain a more precise and consistent view in the interpretation of sharia transactions. It is hoped that the results of this study can provide benefits for BMT in improving sharia consistency in the development of assets with gold investment financing.